PENDAMPINGAN PENGEMBANGAN BAKAT UNTUK MENINGKATKAN PRESTASI PESERTA DIDIK MI MIFTAHUL ULUM - Abdurrahman; Riki Habibi; Dian Arfani Qirom; Abdul Gafur; Muhammad Iqbal (AlMurtado Journal of Social Innovation and Community Service, 2025)
Improving learner achievement is very important to implement. The implications of learner achievement can contribute to increasing public trust in madrasah. Many madrasah managers are trying to improve their services in order to produce outstanding graduates. There are many problems faced, including the condition of maximum unpreparedness to include students in various events. So optimal assistance is needed to train the talents possessed by each student. This service is carried out with a Participatory Action Research (PAR) approach which is strengthened by the field survey method, analysis of problems that develop in the field, Focus Group Discussion (FGD), SWOT analysis, direct action in the field which consists of a mentoring programme in assisting the development of students' talents which can have implications for increasing student achievement and the image of madrasah. The object of mentoring is talented students at MI Miftahul Ulum. The PKM talent development assistance program is carried out through a gifted student training assistance program according to the competence of each student by setting a mentoring schedule for gifted students which is strengthened by the division of tasks carried out by PKM participants in the Islamic Education Management Study Program, Faculty of Islamic Studies, Nurul Jadid University and at the end with the implementation of assistance to the gifted student promotion program. This assistance provides an effective and efficient contribution in improving student talent on an ongoing basis.